Fabrication of strontium included hafnium oxide thin film based Al/Sr:HfO2/n-Si MIS-Schottky barrier diodes for tuned electrical behavior. (7th October 2021) - Harishsenthil, P.; Chandrasekaran, J.; Thangaraju, D.; Balasubramani, V.
Abstract : Synthesis of Sr included HfO2 for fabrication of a Schottky barrier diode. Abstract : The growth behavior of pure and Sr included HfO2 composite thin films for different concentrations of Sr (5, 10, and 15 Wt%) through the Jet Nebulizer Spray Pyrolysis technique is discussed in detail. The preparation of Al/HfO2 /n-Si and Al/Sr:HfO2 /n-Si Schottky barrier diodes and their rectification behavior were compared. The appearance of intermediate (Sr2 HfO4 ) and new (SrO2 ) phases upon introduction of Sr in HfO2 was recorded through XRD analysis, and particle size enlargement was observed. The absorption coefficients and bandgap energies of pure and Sr included HfO2 films were determined using UV-VIS analysis, and the results imply that the presence of Sr2 HfO4 in Sr:HfO2 increases the overall bandgap from 3.8 to 4.0 eV. The morphology of pure HfO2 was heavily influenced by the presence of Sr; FESEM micrographs revealed that the self-assembled sphere like structure of HfO2 turned into mixed morphology like the rod shape of SrO2 and the contorted spheres of Sr2 HfO4 . EDAX elementary studies have confirmed the presence and percentage changes of Sr, Hf, and O in pure and Sr included composites thin films. The XPS spectrum has confirmed Sr in SrO2 and Sr2 HfO4 phases, and its oxidation states in different phases were verified using short XPS scans. The I – V curves of pure (Al/HfO2 /n-Si) and Sr:HfO2 composite (Al/Sr–HfO2 /n-Si) diodes were studied and compared. The 15% Sr included HfO2 showed higher rectification behavior when compared with pure Al/HfO2 /n-Si and composited (5 and 10%) Al/Sr–HfO2 /n-Si at room temperature.